Expo Pendidikan Pameran Hasil Pertanian dan Peternakan menjadi Aneka Produk di Kecamatan Bajawa: Education Expo: Exhibition of Agricultural and Livestock Products Transformed into Various Products in Bajawa District - Noywuli, Nicolaus; Bao, Antonia Paulina; Reo, Gerardus; Betu, Silverius (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Ngada Regency is an area rich in agricultural and livestock products. Considering the vast potential of STIPER Flores Bajawa as an educational institution, it feels important to advance agriculture and livestock in that area. The purpose of the educational expo is not only to promote the campus but also to provide the community with knowledge and information about processing agricultural and livestock products into various high-value products that can be applied in daily life. The service design involves identifying issues in the processing of agricultural and livestock products, which then determines the expo's objectives and the planning of expo activities, up to the evaluation of the impact of the held expo activities—the technique for collecting data on visitor evaluations of the products involved filling out a questionnaire. The product evaluation data were then analyzed using qualitative descriptive methods. The agricultural and livestock products that have been produced and showcased by STIPER Flores Bajawa at the educational expo include liquid organic fertilizer, cassava and taro chips, JMB (Jahe Merah Bajawa), VCO (Virgin Coconut Oil), plant seedlings, solid organic fertilizer, coffee, purple sweet potato flour, various bamboo accessories, beef jerky, cow skin cracklings, Sui Wu'u, animal feed, salted eggs, laying hen coops, chicken floss, Ra'a Rete Babi, and Sei Babi. Visitors greatly appreciated the product exhibition that had been held, as it was very innovative and served as an inspiration for them to engage in efforts to produce products from agricultural and livestock resources.